Zalabardo on Semantic Unity and Metaphysical Unity. Issue 3 (3rd July 2018) - Johnston, Colin
ABSTRACT: Zalabardo argues that the Tractatus makes an important contribution towards explaining how a representation doesn¹t merely introduce various objects, but furthermore represents them as combined in a certain way. This paper counters that Wittgenstein¹s conceptions of representing and representation preclude the coherence of any such explanatory project.